The rights of psychiatric patients, especially in the field of dementia care - Rita, Zakor-Broda (Magyar Gerontológia, 2023)
Given the demographics of Hungary’s population, the aging process and the change in the age composition project an increasingly worrying future. In an aging society, both the provision of care within the social sector and the provision of specialist care within the health sector are facing an ever-increasing anomaly. The growing number of people over the age of 65, including mostly demented people, as well as people who are limited in self-care and need professional help, must be provided to an increasing extent by the care systems. We are facing a current problem that has affected almost every family directly or indirectly. It is not only the provision of professional care that must be solved for the family members, but also the knowledge of the legal regulation of the special situation during the care, the knowledge of the rights and obligations for the care provider, as well as for the patients and their relatives.